Effects of a vitamin D analog on glycaemic control and immune response in type 1 diabetic children and adolescents from Iran - Ataie-Jafari, Asal (2012)
Type 1 diabetes mellitus (T1DM) results from autoimmune destruction of insulin producing pancreatic β-cells. At the time of T1DM diagnosis, although the majority of β-cells have been destroyed, some still produce insulin. A treatment that could protect β-cell function or decrease autoimmune destruction would provide important progress in T1DM therapy. Vitamin D has been known as an immunomodulator in this disease, which blockades β-cells destruction. In children with T1DM, vitamin D treatment produces moderate protective effects on residual β-cell function. However,limited doses can be used because of its hypercalcemic effect. This study investigated whether treatment with a vitamin D analog (1-α-hydroxyvitamin D3) or alfacalcidol, can improve glycemic control and B-cell preservation, as well as improvements in immune responses. In this single-blind and placebo-controlled clinical trial, 60 patients (aged 8-18 years) with recent-onset T1DM were randomized to alfacalcidol (2 β 0.25 βg/day) or placebo, and followed up for 6 months. All patients received conventional insulin therapy, and insulin dosage was adjusted every two weeks. Dietary vitamin D intakes and sun exposure were assessed at baseline. Insulin requirement, as well as serum 25(OH)D, fasting Cpeptide (FCP), hemoglobin A1C (HbA1C), interleukin-1β (IL-1β), interleukin-2 (IL-2), transforming growth factor β1 (TGF-β1), interferon-gamma (IFN-γ), and glutamic acid decarboxylase (GAD65) autoantibody were assessed at baseline, and again 3 months and 6 months after the intervention. Repeated measures ANOVA was used to compare the alfacalcidol and placebo groups across time points during 6 months of intervention. Fifty-three patients completed the study. All patients were vitamin D deficient (77%) or insufficient (23%) at baseline. In a logistic regression model, it was shown that the risk of being vitamin D deficient was significantly decreased by sunlight exposure β 15 minutes during the weekends versus < 15 minutes (odds ratio [OR]: 0.059 [95% confidence interval [CI]: 0.01–0.75]; P=0.03). Serum 25(OH)D dropped 19.7% and 39.2% in alfacalcidol and placebo group respectively, however the difference between groups was not significant [F(1,51)=1.69; P= 0.195]. HbA1C also decreased in both groups throughout the study as expected. Serum levels of FCP increased in both groups after 3 months of study, and then dropped from 0.49 ± 0.18 to 0.33 ± 0.15 ng/ml during moth 3 to month 6 (P=0.003; unpaired t-test) in the placebo group, however it remained unchanged in the alfacalcidol group (P > 0.05). Insulin requirement per body weight did not change significantly in the placebo group; however, it decreased in the alfacalcidol group during the first two months of study, and then increased slightly by the end of 6 months follow-up. Changes of insulin requirement per body weight was significant across groups over 6 months of intervention [F(1,51)= 4.2; P= 0.017)]. Serum levels of IL-1β was unchanged in the placebo group, but decreased in the alfacalcidol group throughout the study. Changes of serum IL-1β was significant across groups over 6 months of intervention [F(1,51)= 4.88, P= 0.010]. Serum oncentrations of IL-2 did not change significantly in the alfacalcidol group during 6 months of the study (Friedman test, P= 0.169), but the trend of changes was highly significant in the placebo group (Friedman test, P < 0.001). The two-way repeated measures ANOVA also showed significant differences in serum TGF-β1, IFN-across groups over 6 months of intervention [F(1,51)= 4.2; P= 0.017)]. Serum levels of IL-1β was unchanged in the placebo group, but decreased in the alfacalcidol group throughout the study. Changes of serum IL-1across groups over 6 months of intervention [F(1,51)= 4.2; P= 0.017)]. Serum levels of IL-1β was unchanged in the placebo group, but decreased in the alfacalcidol group throughout the study. Changes of serum IL-1β was significant across groups over 6 months of intervention [F(1,51)= 4.88, P= 0.010]. Serum concentrations of IL-2 did not change significantly in the alfacalcidol group during 6 months of the study (Friedman test, P= 0.169), but the trend of changes was highly significant in the placebo group (Friedman test, P < 0.001). The two-way repeated measures ANOVA also showed significant differences in serum TGF-β1, IFN-β, and GAD65 autoantibody changes between the alfacalcidol and the placebo group during 6 months of study (P= 0.045, P= 0.006, P= 0.006; respectively, for interaction between time and group). Serum TGF-β1 dropped from 115.5 ± 35.5 to 89.3 ± 35 pg/ml in the placebo group over 6 months of intervention (P= 0.012), but it remained unchanged in the alfacalcidol-treated patients. Conversely, serum IFN-β was unchanged in the alfacalcidol group during 6 months of trial, but increased significantly in the placebo group. Serum levels of GAD65 autoantibody decreased in both groups, with a higher rate in the alfacalcidol-treated patients. Six months treatment of newly diagnosed T1DM children with 1-α-(OH)D3 seems to preserve across groups over 6 months of intervention [F(1,51)= 4.2; P= 0.017)]. Serum levels of IL-1β was unchanged in the placebo group, but decreased in the alfacalcidol group throughout the study. Changes of serum IL-1β was significant across groups over 6 months of intervention [F(1,51)= 4.88, P= 0.010]. Serum concentrations of IL-2 did not change significantly in the alfacalcidol group during 6 months of the study (Friedman test, P= 0.169), but the trend of changes was highly significant in the placebo group (Friedman test, P < 0.001). The two-way repeated measures ANOVA also showed significant differences in serum TGF-β1, IFN-β, and GAD65 autoantibody changes between the alfacalcidol and the placebo group during 6 months of study (P= 0.045, P= 0.006, P= 0.006; respectively, for interaction between time and group). Serum TGF-β1 dropped from 115.5 ± 35.5 to 89.3 ± 35 pg/ml in the placebo group over 6 months of intervention (P= 0.012), but it remained unchanged in the alfacalcidol-treated patients. Conversely, serum IFN-β was unchanged in the alfacalcidol group during 6 months of trial, but increased significantly in the placebo group. Serum levels of GAD65 autoantibody decreased in both groups, with a higher rate in the alfacalcidol-treated patients. Six months treatment of newly diagnosed T1DM children with 1-α-(OH)D3 seems to preserve β-cells function, and result in lower insulin requirement probably through induction of a shift from Th-1 to Th-2 cytokines produced by the autoimmune T cells.β-cells function, and result in lower insulin requirement probably through induction of a shift from Th-1 to Th-2 cytokines produced by the autoimmune T cells. was significant across groups over 6 months of intervention [F(1,51)= 4.88, P= 0.010]. Serum oncentrations of IL-2 did not change significantly in the alfacalcidol group during 6 months of the study (Friedman test, P= 0.169), but the trend of changes was highly significant in the placebo group (Friedman test, P < 0.001). The two-way repeated measures ANOVA also showed significant differences in serum TGF-β1, IFN-β, and GAD65 autoantibody changes between the alfacalcidol and the placebo group during 6 months of study (P= 0.045, P= 0.006, P= 0.006;respectively, for interaction between time and group). Serum TGF-β1 dropped from 115.5 ± 35.5 to 89.3 ± 35 pg/ml in the placebo group over 6 months of intervention (P= 0.012), but it remained unchanged in the alfacalcidol-treated patients. Conversely, serum IFN-β was unchanged in the alfacalcidol group during 6 months of trial, but increased significantly in the placebo group. Serum levels of GAD65 autoantibody decreased in both groups, with a higher rate in the alfacalcidol-treated patients. Six months treatment of newly diagnosed T1DM children with 1-α-(OH)D3 seems to preserve β-cells function, and result in lower insulin requirement probably through induction of a shift from Th-1 to Th-2 cytokines produced by the autoimmune T cells., and GAD65 autoantibody changes between the alfacalcidol and the placebo group during 6 months of study (P= 0.045, P= 0.006, P= 0.006; respectively, for interaction between time and group). Serum TGF-β1 dropped from 115.5 ± 35.5 to 89.3 ± 35 pg/ml in the placebo group over 6 months of intervention (P= 0.012), but it remained unchanged in the alfacalcidol-treated patients. Conversely, serum IFN-β was unchanged in the alfacalcidol group during 6 months of trial, but increased significantly in the placebo group. Serum levels of GAD65 autoantibody decreased in both groups, with a higher rate in the alfacalcidol-treated patients. Six months treatment of newly diagnosed T1DM children with 1-α-(OH)D3 seems to preserve β-cells function, and result in lower insulin requirement probably through induction of a shift from Th-1 to Th-2 cytokines produced by the autoimmune T cells.